2013
DOI: 10.1002/ange.201302693
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Intracellular Pathogenic Bacteria with Unnatural Proline‐Rich Peptides: Coupling Antibacterial Activity with Macrophage Penetration

Abstract: Das De‐novo‐Design nichtnatürlicher prolinreicher Peptide führt zu einem Wirkstoff gegen sowohl Gram‐positive als auch Gram‐negative Bakterien. Dieses Peptid löst weder bakterielle Membranen auf, noch bewirkt es eine Hämolyse; überdies ist es über längere Zeit gegen Trypsin stabil. Das leichte Eindringen in Makrophagen führt zu einer gründlichen Beseitigung pathogener Bakterien in diesen Zellen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…P14LRR peptide and the peptide kanamycin conjugate (P14KanS) ( Fig. 1) were synthesized as described previously [13,14].…”
Section: Bacterial Isolates Drugs and Reagentsmentioning
confidence: 99%
See 1 more Smart Citation
“…P14LRR peptide and the peptide kanamycin conjugate (P14KanS) ( Fig. 1) were synthesized as described previously [13,14].…”
Section: Bacterial Isolates Drugs and Reagentsmentioning
confidence: 99%
“…1). P14LRR is a small de novo proline rich antimicrobial peptide that forms a cationic amphiphilic polyproline helix and demonstrates broad-spectrum efficacy against pathogenic bacteria [13,14]. P14LRR is non-hemolytic and highly stable to proteases.…”
Section: Introductionmentioning
confidence: 99%
“…Brezden et al recently reported interesting conjugates (Figure ), consisting of the aminoglycoside antibiotic kanamycin ( 85 ) with the CPP P14LRR ( 86 ), which when conjugated exhibited potent ATB activity against these intracellular pathogens . The CPP ( 86 ) previously demonstrated intrinsic ATB activity against intracellular Salmonella and Brucella bacteria . In Brezden et al's study, kanamycin ( 85 ) was linked to ( 86 ), with or without a cleavable disulfide linkage, to form the conjugates ( 87 ) and ( 88 ) (Figure ).…”
Section: Trojan Horse Approaches To Overcome Antimicrobial Resistancementioning
confidence: 99%
“…211 The CPP (86) previously demonstrated intrinsic ATB activity against intracellular Salmonella and Brucella bacteria. 212 In Brezden et al's study, kanamycin (85) was linked to (86), with or without a cleavable disulfide linkage, to form the conjugates (87) and (88) (Figure 16). This attachment increased the overall net positive charge of the conjugates (from +8 to +12), therefore, facilitating the penetration and accumulation of the drug into J774A.1 host cells.…”
mentioning
confidence: 99%
“…BnPRP1 from Brassica napus ( Figure 3 c) like many other proline-rich AMPs (PrAMPs) forms random coils with little amount of α-helix composition that engage in a non-lytic modes of bacterial inactivation [ 69 ]. Since proline is incompatible with α-helical or β-sheet conformation, its frequent occurrence in a polypeptide sequence causes a conformational rearrangement that forces the molecule to adopt the polyproline II (PPII) helical structure [ 70 , 71 , 72 ] and ample evidence suggest that the PPII conformation may be the biologically active form for all PrAMP [ 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Diverse Sources Of Ampsmentioning
confidence: 99%